Combination immunotherapy of chlorogenic acid liposomes modified with sialic acid and PD-1 blockers effectively enhances the anti-tumor immune response and therapeutic effects. (1st January 2021) - Li, Xixi; Zhu, Shunyao; Yin, Ping; Zhang, Shuangshuang; Xu, Juewen; Zhang, Qin; Shi, Senlin; Zhang, Ting
Abstract: Melanoma is one of the most common malignant tumors. The anti-PD-1 antibody is used for the treatment of metastatic melanoma. Treatment success is only 35–40% and a range of immune-related adverse reactions can occur. Combination of anti-PD1 antibody therapy with other oncology therapies has been attempted. Herein, we assessed whether chlorogenic acid liposomes modified with sialic acid (CA-SAL) combined with anti-PD1 antibody treatment was efficacious as immunotherapy for melanoma. CA-SAL liposomes were prepared and characterized. In a mouse model of B16F10 tumor, mice were treated with an anti-PD1 antibody, CA-SAL, or combination of CA-SAL + anti-PD1 antibody, and compared with no treatment controls. The tumor inhibition rate, tumor-associated macrophages (TAMs) phenotype, T-cell activity, and safety were investigated. We observed a significant decrease in the proportion of M2-TAMs and CD4 + Fop3 + T cells, while there was a significant increase in the proportion of M1-TAMs and CD8 + T cells, and in the activity of T cells, and thus in the tumor inhibition rate. No significant toxicity was observed in major organs. CA-SAL and anti-PD1 Ab combination therapy presented synergistic anti-tumor activity, which enhanced the efficacy of the PD-1 checkpoint blocker in a mouse model of melanoma. In summary, combination immunotherapy of CA-SAL and anti-PD1 Ab has broad prospects in improving the therapeutic effect of melanoma, and may provide a new strategy for clinical treatment. Graphical Abstract: UF0001